Review of Influenza A Virus in Swine Worldwide: A Call for Increased Surveillance and Research - Vincent, A. (2013)
Pigs and humans have shared influenza A viruses (IAV) since at least 1918, and many interspecies transmission events have been documented since that time. However, despite this interplay, relatively little is known regarding IAV circulat- ing in swine around the world compared with the avian and human knowledge base. This gap in knowledge impedes our understanding of how viruses adapted to swine or man impacts the ecology and evolution of IAV as a whole and the true impact of swine IAV on human health. The pandemic H1N1 that emerged in 2009 underscored the need for greater surveillance and sharing of data on IAV in swine. In this paper, we review the current state of IAV in swine around the world, highlight the collaboration between international organizations and a network of laboratories engaged in human and animal IAV surveillance and research, and emphasize the need to increase information in high-priority regions. The need for global integration and rapid sharing of data and resources to fight IAV in swine and other animal species is apparent, but this effort requires grassroots support from governments, practicing veterinarians and the swine industry and, ultimately, requires significant increases in funding and infrastructure.